Safety and efficacy of filgotinib in patients with rheumatoid arthritis: final results of the DARWIN 3 long-term extension study - Arthur Kavanaugh; Paul Emery; René Westhovens; Mark C Genovese; Kevin L Winthrop; Rieke Alten; Dick de Vries; Lorenzo Dagna; Patrick Verschueren; Maria Greenwald; Regina Cseuz; Robin Besuyen; et al. (RMD Open)
Objectives DARWIN 3 (ClinicalTrials.gov: NCT02065700) assessed the safety and efficacy of filgotinib in a long-term extension (LTE) of two phase II randomised controlled rheumatoid arthritis (RA) trials.Methods Eligible patients completing the 24-week DARWIN 1 (filgotinib plus methotrexate) and DARWIN 2 (filgotinib monotherapy) trials could enrol. Patients received filgotinib 200 mg/day, except 15 men who received filgotinib 100 mg/day. The primary endpoints were safety and tolerability, which were assessed by the incidence of treatment-emergent adverse events (TEAEs). Safety and efficacy analyses included all enrolled patients who received ≥1 dose of filgotinib in DARWIN 3.Results 739 patients entered the LTE. The total patient-years of exposure (PYE) to filgotinib was 3706.3 years; the mean exposure duration was 259.8 weeks. 497 patients (67.3%) discontinued prematurely (including 266 TEAEs and 172 withdrawals due to the patient’s decision or ‘sponsor request’). Overall exposure-adjusted incidence rate (EAIR) was 67 (95% CI 62 to 72.2)/100 PYE for TEAEs and 3.8 (95% CI 3.2 to 4.5)/100 PYE for serious TEAEs. EAIR of infections was 23.3 (95% CI 21.2 to 25.6)/100 PYE, 1.3 (95% CI 0.9 to 1.7)/100 PYE for serious infections and 1.3 (95% CI 0.9 to 1.7)/100 PYE for herpes zoster. EAIRs of major adverse cardiovascular events (0.19 (95% CI 0.8 to 0.39)/100 PYE) and malignancies (0.6 (95% CI 0.4 to 0.9)/100 PYE) were low. Disease response assessed using non-responder imputation plateaued at LTE week 12 before slowly declining over time, with overall American College of Rheumatology (ACR)20/50/70 response rates of 26.9%/20.2%/14.7% at week 396.Conclusion Filgotinib was well tolerated in patients with RA for up to 8 years. Safety and efficacy profiles were maintained in patients previously receiving either filgotinib plus methotrexate or filgotinib monotherapy.